Abordagem semiótica dos elementos totalitaristas em O castelo, de Franz Kafka - Viana, Karen Bernardo (2021)
This dissertation work explores the totalitarian regime, specifically totalitarian elements, in order to see how and what elements are manifested in the novel The Castle (2008), by Franz Kafka. To conduct this study, we used discursive semiotic theory, Barros (2001, 2005, 2008 and 2011), Bueno (2006), Fiorin (2013 and 2014), Fontanille (2016), Greimas (2014) and Greimas and Courtés (2018), principally. In order to study totalitarianism, we restricted the research - given the complexity that would be to study a government regime - by using three great theorists of totalitarianism, Arendt (1989) and Friedrich and Brzezinski (1965). From the study of the authors, with the discursive semiotic method, we inferred characteristics of the totalitarian regime, which we called totalitarian elements, resulting in a framework of elements, with which it will be possible to study the corpus. The elements are manifested, thematized and figurativeized, in the most diverse speeches. In the case of our text under analysis, The Castle (2008), we found that there are more themes than figures, which makes the novel look like a philosophical text. Furthermore, the relations between enunciator and enunciatee indicate that the enunciator seeks to hide /knowledge/, always proposing to the enunciatee the regime of /believe/, so that the text only makes sense to the one who believes. Thus, the annunciator can be compared to the Castle itself of the novel that holds all / power / and whose servants only have to accept and believe.